2020
DOI: 10.1111/mpp.12898
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant haplotypes of avirulence genes of Phytophthora sojae lead to a molecular assay to predict phenotypes

Abstract: The soybean–Phytophthora sojae interaction operates on a gene‐for‐gene relationship, where the product of a resistance gene (Rps) in the host recognizes that of an avirulence gene (Avr) in the pathogen to generate an incompatible reaction. To exploit this form of resistance, one must match with precision the appropriate Rps gene with the corresponding Avr gene. Currently, this association is evaluated by phenotyping assays that are labour‐intensive and often imprecise. To circumvent this limitation, we sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…Thus, the detection of mutations in cloned Avr probe genes may not be sufficient for a virulent profile prediction of filed isolates. This is different from the scenario of P. sojae, in which the presence of functional Avr genes in selected isolates is highly consistent with their avirulent phenotype [30]. Moreover, co-expression of Avrvnt1 and Rpi-vnt1 or single Avrvnt1 failed to induce HR in S. pinnatisectum, suggesting that specific interacting proteins are needed for Avrvnt1-Rpi-vnt1 recognition.…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, the detection of mutations in cloned Avr probe genes may not be sufficient for a virulent profile prediction of filed isolates. This is different from the scenario of P. sojae, in which the presence of functional Avr genes in selected isolates is highly consistent with their avirulent phenotype [30]. Moreover, co-expression of Avrvnt1 and Rpi-vnt1 or single Avrvnt1 failed to induce HR in S. pinnatisectum, suggesting that specific interacting proteins are needed for Avrvnt1-Rpi-vnt1 recognition.…”
Section: Discussioncontrasting
confidence: 73%
“…Interestingly, all five cases of discrepancy were present in the Avr3a gene. The PCR amplification for the avirulent alleles of Avr3a was achieved in the five cases, but the compatible interactions with Rps3a were observed in the phenotyping assay (Dussault-Benoit et al, 2020). Avr3a is a RXLR effector gene and encodes a predicted protein of 111 amino acids that includes a signal peptide, a RXLR motif and a carboxyterminal effector domain (Qutob et al, 2009;Dong et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the development of simple and rapid molecular diagnostic methods is the main tendency for pathotype identification. More recently, Dussault-Benoit et al (2020) developed a molecular assay that could define P. sojae pathotypes using seven Avr genes ( Avr1a , Avr1b , Avr1c , Avr1d , Avr1k , Avr3a , and Avr6 ). The matching rate between the molecular assay and the phenotyping assay was as high as 97% (170/175).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism analysis indicated that there were five Virulence structure of P. sojae should be constantly monitored to determine and deploy effective Rps genes (Dorrance et al, 2016;Stewart et al, 2016). Conventional virulence tests are labor-intensive and time-consuming, thus a rapid and simple PCR assay for pathotype identification of P. sojae was developed (Dussault-Benoit et al, 2020). However, when the PCR assay was used to detect the virulence of isolate Ps0903 with Avr3a(IV) to Rps3a in this study, a false positive result occurred.…”
Section: Discussionmentioning
confidence: 80%